Republic of Tajikistan : Joint Staff Advisory Note of the Poverty Reduction Strategy Paper Second Progress Report. (IMF Staff Country Reports; Country Report ;, 2006)
This Joint Staff Advisory Note discusses the Poverty Reduction Strategy Paper (PRSP) Second Progress Report for the Republic of Tajikistan. The progress report presents a comprehensive assessment of the nature and dynamics of poverty from various sources and perspectives, and recognizes the challenges ahead for continued progress in reducing the number of people living in poverty. The report fully acknowledges that the poor quality, reliability, and timeliness of statistics for monitoring progress in poverty reduction are owed to the lack of capacity to collect and analyze data and to the weak coordination between state agencies.